2001
DOI: 10.1114/1.1366674
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Dipole Source Imaging of Brain Electric Activity by Means of Parametric Projection Filter

Abstract: In the present study, spatial filters for inverse estimation of an equivalent dipole layer from the scalp-recorded potentials have been explored for their suitability in achieving high-resolution electroencephalogram (EEG) imaging. The performance of the parametric projection filter (PPF), which we propose to use for high-resolution EEG imaging, has been evaluated by computer simulations in the presence of a priori information on noise. An inhomogeneous three-concentric-sphere head model was used in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…In these cases, our proposed method can demonstrate the behavior of individual sources using equivalent dipole distribution. We confirmed that several dipole sources could be represented by the PPFbased inverse filters [15]- [17] and the PWF-based inverse filter [21].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In these cases, our proposed method can demonstrate the behavior of individual sources using equivalent dipole distribution. We confirmed that several dipole sources could be represented by the PPFbased inverse filters [15]- [17] and the PWF-based inverse filter [21].…”
Section: Discussionsupporting
confidence: 73%
“…In actual situation, cortical sources may have a strong tangential component. The brain electrical activity caused by the tangential dipole sources could also be represented with the strength distribution of radial dipoles [15]. When some dipole sources simultaneously exist in the brain, the distributions caused by each source may be overlapped on the scalp map.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The parametric projection filter (PPF), satisfying Eq. (7.26), is derived by (Oja and Ogawa, 1986;Ogawa and Oja, 1987;Hori and He, 2001) 5ppF = A^(A4^ + Ae)+ (7.27) Note, the PPF is a special case of the PWF, when R -I in Eq. (7.23).…”
Section: 325 Projection Filter and Parametric Projection Filtermentioning
confidence: 99%